THE IMPACT OF ENSO PHENOMENA ON ELECTRICITY PRODUCTION AT MRICA HYDROELECTRIC POWER PLANT IN CENTRAL JAVA (2013-2023) - Kevin Sahat Parsaulian; Muhammad Rais Abdillah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the impact of the El Niño Southern Oscillation (ENSO) on electricity production at the Mrica Hydroelectric Power Plant (PLTA Mrica) in Central Java from 2013 to 2023. ENSO is global climate phenomenon, influences rainfall and ocean circulation in various regions, including Indonesia. Data on rainfall and river discharge from the Serayu River were analyzed to determine how ENSO affects the operational efficiency of PLTA Mrica. The study reveals that strong El Niño events, such as those in 2015, significantly reduced river discharge, leading to decreased electricity production. Conversely, the La Niña event in 2020 increased river discharge, enhancing electricity production. The findings underscore the critical need for adaptive water resource management and continuous monitoring to optimize electricity generation at PLTA Mrica, particularly in the face of climate variability induced by ENSO. This research contributes to understanding the relationship between climate phenomena and hydroelectric power generation.